The Deuchny Hill Fort: The Chalmers-Jervise Prize essay (Proceedings of the Society of Antiquaries of Scotland, 1923)
A detailed plan of the hill fort is presented. Examination of the highest part shows that though the natural formation is almost entirely rock, there is evidence of a more or less continuous rampart or wall along the edge of the plateau on the top of the hill. The entrance or gateway is at the south-east end. There is no indication of any water supply, unless it be one or two places where there seem to be earth-filled hollows. Surface finds include a mortar and a fragment of a jet armlet.